Perawatan Pasien dengan Diagnosa KO4 (Kelainan Pulpa dan Jaringan Periapikal) di Puskesmas Kencong, Puskesmas Jenggawah, dan RSUD dr. H. Koesnadi Bondowoso - Kiswaluyo Kiswaluyo; Faridlotul Imaniyah; Iriana Fitiariski; Eva Latifah; Ratih Mahanani; Fama Alburuda; Nyimas Amalia (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2015)
Frequency of dental caries in Indonesia in 2004 reached 90.05% with the state of the teeth can be apical tooth tissue disorders, gangrene pulp, gangrene radix, pulpitis, hyperemia pulp and pulp irritation. The treatment can be done in cases of pulp and periapical tissues were extracted and sterilization. The research was to determine the type of treatment that is done for cases of pulp and periapical tissues in health centers and hospitals. This type of study was an observational cross-sectional approach. The data was recorded from data of patients who come to visit Dental's clinic in Puskesmas Kencong, Puskesmas Jenggawah, and Bondowoso Hospital. The case of pulp disorders and periapical tissues, health centers's treatment was more extraction preceded by medication or not and hospital's treatment was more performed sterilization will be made permanent restoration.